INTEGRATING THE INDUAK SAMANG-ANAK SAMANG PHILOSOPHY INTO A PSYCHOEDUCATIONAL MODEL TO ENHANCE THE EMPLOYABILITY SKILLS OF VOCATIONAL SCHOOL STUDENTS - Elfira, Yenni; Neviyarni, Neviyarni; Afdal, Afdal (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Vocational high school graduates in Indonesia face the highest unemployment rates, largely due to deficient employability skills. This study developed and validated the BIDASAN psychoeducational model a culturally responsive intervention rooted in the Minangkabau "Induak Samang-Anak Samang" philosophy to strengthen vocational students' career readiness. Following the ADDIE instructional design model, a needs analysis was conducted with 322 students in West Sumatra, followed by a quasi-experimental trial with 20 students at Vocational secondary education 1 Enam Lingkung. Data were collected using a 63-item validated employability scale and analyzed via paired and independent sample t-tests. Expert validation (85.33%) and practitioner practicality (87%) confirmed the model's high feasibility. The experimental group showed a significant improvement in employability skills (N-Gain 0.38) compared to the control group (N-Gain 0.21). The BIDASAN model effectively bridges the gap between cultural values and professional demands, offering a novel approach for school counselors to reduce graduate unemployment.